Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Motivasi Belajar Siswa - Lalu Muhammad Maqbul Alghifari; Harmanto Harmanto; Achmad Zaini (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2023)
Research has been conducted on the Application of Problem Based Learning Models to Increase Student Learning Motivation in class VII J SMPN 45 Surabaya. This research is a classroom action research with the results of research that the application of problem based learning, learning models can increase student learning motivation. This is evident from the results of research observations after applying the Problem Based Learning learning model, student learning motivation increased from 47% in cycle I to 71% in cycle II. Furthermore, the results of the learning motivation questionnaire increased from 53% in cycle I to 79% in cycle II. So that student learning motivation that was previously in the low category increased to motivation in the high learning motivation category.